The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1097/00001756-200004070-00035
|View full text |Cite
|
Sign up to set email alerts
|

Neurons and ECM regulate occludin localization in brain endothelial cells

Abstract: We report that extracellular matrix and neurons modulate the expression of occludin, one of the main components of tight junctions, by rat brain endothelial cells (RBE4.B). Of the three extracellular matrix proteins which we tested (collagen I, collagen IV, and laminin), collagen IV stimulated at the best the expression of occludin mRNA. The corresponding protein, however, was not synthesized. Significant amounts of occludin accumulated only when RBE4.B cells were cultured on collagen IV-coated inserts, in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(88 citation statements)
references
References 6 publications
1
85
0
Order By: Relevance
“…It also implies that endothelial cells in the in vitro model may be more sensitive to H and H/R due to the lack of pericytes, glia, and neurons, which constitute the intact neurovascular unit. This concept is supported by studies (2,27,42,43) that show that endothelial cells co-cultured with glia and/or neurons respond differently to stimuli than do endothelial cells cultured alone. A second explanation for the differences between the in vitro and in vivo H models may be the level of H and duration of the hypoxic exposure.…”
Section: Discussionmentioning
confidence: 87%
“…It also implies that endothelial cells in the in vitro model may be more sensitive to H and H/R due to the lack of pericytes, glia, and neurons, which constitute the intact neurovascular unit. This concept is supported by studies (2,27,42,43) that show that endothelial cells co-cultured with glia and/or neurons respond differently to stimuli than do endothelial cells cultured alone. A second explanation for the differences between the in vitro and in vivo H models may be the level of H and duration of the hypoxic exposure.…”
Section: Discussionmentioning
confidence: 87%
“…We previously found that both neurons (24,27,28) and astrocytes (23,24) influence the ability of endothelial cells to form a barrier with properties resembling those of BBB. In the present study, we used an already described BBB in vitro model (23,24) to investigate whether the serum from patients with secondary progressive multiple sclerosis (SPMS) (29) caused any alteration of the neuronal vitality and morphology, and/or any BBB damage.…”
Section: Resultsmentioning
confidence: 99%
“…Cells were homogenized in homogenization buffer (0.32 M sucrose; 50 mM sodium phosphate buffer, pH 6.5; 50 mM KCl, 0.5 mM spermine; 0.15 mM spermidine; 2 mM EDTA, and 0.15 mM EGTA), containing the protease inhibitors aprotinin (2 μg/ml), antipain (2 μg/ml), leupeptin (2 μg/ml), pepstatin A (2 μg/ml), benzamidine (1.0 mM) and phenylmethylsulfonyl fluoride (1.0 mM), all purchased from Sigma-Aldrich. Proteins (20 μg of total cell extracts) were separated by electrophoresis on denaturing 10% polyacrylamide slab gels (SDS-PAGE) and immunoblotted as described elsewhere (27). The membranes were immunostained with goat polyclonal anti-occludin N19 antibodies (Santa Cruz).…”
Section: Methodsmentioning
confidence: 99%
“…There is some evidence that neurons contribute directly to the induction of tight junction formation during development. Proper targeting of occludin, one of the proteins that constitute tight junctions in endothelial cells, to the cell periphery has been shown to occur only after co-culture with neurons [133]. There is evidence for a synergistic effect on tight junction formation when astrocytes and neurons are cultured with endothelial cells [134].…”
Section: B Tight Junction Proteinsmentioning
confidence: 99%
“…There is evidence for a synergistic effect on tight junction formation when astrocytes and neurons are cultured with endothelial cells [134]. Neurons in combination with extracellular matrix components can also play a role in regulation of occludin expression [133]. Neuronal activity is closely coupled with astrocyte and blood vessel functions in the brain.…”
Section: B Tight Junction Proteinsmentioning
confidence: 99%